2014
DOI: 10.1016/j.sdentj.2014.03.006
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of dental caries among 12–14year old children in Qatar

Abstract: Results indicated that dental caries prevalence among school children in Qatar has reached critical levels, and is influenced by socio-demographic factors. The mean decayed, missing, and filled teeth values obtained in this study were the second highest detected in the Eastern Mediterranean region.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

19
78
4
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(105 citation statements)
references
References 26 publications
19
78
4
4
Order By: Relevance
“…The finding was in accordance with a study done by Shailee et al 26 where they had 626 males and 385 females. Findings of Johansson et al, 27 Al-Darwish et al, 28 Sood et al, 29 Dhar et al, 30 Sudha et al, 31 and Singh et al 32 were also in agreement to our study where greater preponderance was observed for males because females were getting lesser opportunity to get proper education, mainly in rural areas, than males in developing countries like India, whereas studies by Mtaya et al, 33 Khanal and …”
Section: Discussionsupporting
confidence: 90%
“…The finding was in accordance with a study done by Shailee et al 26 where they had 626 males and 385 females. Findings of Johansson et al, 27 Al-Darwish et al, 28 Sood et al, 29 Dhar et al, 30 Sudha et al, 31 and Singh et al 32 were also in agreement to our study where greater preponderance was observed for males because females were getting lesser opportunity to get proper education, mainly in rural areas, than males in developing countries like India, whereas studies by Mtaya et al, 33 Khanal and …”
Section: Discussionsupporting
confidence: 90%
“…This finding is in agreement with data from a study conducted in Australian indigenous children, which reported that living in a rural location was the strongest indicator of caries prevalence, severity and unmet treatment needs in the primary dentition (6). A similar trend has been observed in studies conducted with non-indigenous children from Brazil and Qatar, where children residing in urban areas had lower mean DMFT indices, a significantly lower risk of dental caries and reported significantly fewer toothaches and greater use of dental services than those residing in semi-urban/ rural areas (18,19). Actions of the dental team in the Xukuru community are evident, especially given the considerable proportion of the filled component among permanent teeth.…”
Section: Discussionsupporting
confidence: 62%
“…Bivariate analyses were performed to determine associations between the independent and dependent variables. Variables with a P-value <0.20 in the bivariate analysis as well as those considered epidemiological determinants (age group, group of villages, breastfed, bottle fed, consumption of sugar, oral hygiene frequency, mother's schooling and monthly household income) (16)(17)(18)(19) were incorporated into the multiple regression models in ascending order of their p-values (20). Variables with a P-value <0.05 were maintained in the final regression models.…”
Section: Discussionmentioning
confidence: 99%
“…Nibras and his colleagues found DC prevalence to be 62% among 12-year-old schoolchildren in Baghdad, Iraq [26]. The prevalence of DC among 12-14 year old children in Qatar was found to be 85% [27].…”
Section: Global Burden Of Dental Cariesmentioning
confidence: 99%